Vasoactive inotropic score as a prognostic factor during (cardio-) respiratory ECMO - Sandrio, Stany; Krebs, Jörg; Leonardy, Eva; Thiel, Manfred; Schöttler, Jochen (Journal of Clinical Medicine, 2022)
The vasoactive inotropic score (VIS) is calculated as a weighted sum of all administered vasopressor and inotropic medications and quantifies the amount of pharmacological cardiovascular support in patients with the most severe combined cardiopulmonary failure supported with extracorporeal membrane oxygenation (ECMO). This study evaluated (1) whether VIS prior to the initiation of ECMO is an independent predictor of survival in these patients and (2) whether VIS might guide the selection of the appropriate extracorporeal cannulation modality (Veno-Venous ‘V-V’ or Veno-VenoArterial ‘V-VA’). In this study, 39 V-VA and 182 V-V ECMO runs were retrospectively analyzed. VIS immediately prior to ECMO initiation (pre-ECMO) was 40 (10/113) in all patients, 30 (10/80) in patients with V-V ECMO and 207 (60/328) in patients with V-VA ECMO. Pre-ECMO VIS was an independent predictor of survival in univariate (AUC = 0.68, p = 0.001) and multi-variable analyses (p = 0.02). Pre-ECMO VIS was clearly associated with mortality (p = 0.001) in V-V ECMO group; however, V-VA ECMO disrupted this association (p = 0.18). Therefore, in conjunction with echocardiography, VIS might assist in selecting the appropriate ECMO cannulation strategy as patients with a pre-ECMO VIS ≥ 61.4 had significantly lower odds of survival compared to those with lower VIS.
Gesehen am 15.06.2022